Effects of adopting IFRS 10 and IFRS 11 on consolidated financial statements: An exploratory research. Issue 1 (7th January 2019) - Lopes, Ana Isabel; Lopes, Mariana
Abstract : Purpose: The purpose of this paper is to investigate how the adoption of IFRS 10 and IFRS 11 affected consolidated financial statements. Specifically, the paper explores whether entities adopted mandatorily or voluntarily both IFRS, whether expressly declared effects, whether considered those effects as material and whether those effects had impacts on selected items of financial statements and on selected financial ratios. Design/methodology/approach: The research is an exploratory study using public entities from Germany, France and the UK. The majority of the data is manually collected from financial statements. Findings: The results suggest that the adoption of the new IFRS 10 affected the composition of a large number of entity groups but that their financial information and economic-financial indicators do not present material changes. There is also evidence of a large and material impact on the changes in the classification and accounting for interests in arrangements under joint control through the new IFRS 11. The evidence thus suggests unequal effects of the adoption of IFRS 10 and IFRS 11 on the proportion of entities declaring materiality of effects, on the quantitative effects on selected items of financial statements, and on financial ratios. A comparison between the pre-adoption and post-adoption periods reveals that the majority of the effects are driven by the adoption of IFRS 11. Originality/value: As far as is known this exploratory paper is the first presenting the effectiveness of adopting the most important standards under the "consolidation package" and opens an avenue for future research by academics, for future post-implementation reviews by IASB, and for analysis of peer reviews between accounting practitioners.